Debate on the New Global Capitalism: Transnational Capitalist Class, Transnational State Apparatuses, and Global Crisis. Issue 2 (3rd April 2017) - Robinson, William I.
ABSTRACT: The state-centrism and nation-state/inter-state framework that reifies and fetishizes the nation-state and informs much theorization and analysis of world politics, political economy, and class structure is ever more incongruent with twenty-first century world developments. An epochal shift is underway to a new phase in the on-going and open-ended evolution of world capitalism, global capitalism, characterized by the rise of truly transnational capital and the integration of every country into a new globalized system of production and finance, a transnational capitalist class as would be global ruling class, and transnational state apparatuses. The anomalies in traditional approaches demonstrate the need for a Kuhnian paradigm shift. Competition among capitals and international conflicts are endemic to the system yet competition takes on new forms in the age of globalization not necessarily expressed as national rivalry. Global capitalism is in crisis. The more enlightened strata of the transnational elite want stronger transnational state apparatuses in order to cement the rule of the transnational capitalist class, bring a measure of regulation and governance from above, and stabilize the crisis-ridden system. A global rebellion against the transnational capitalist class is underway but popular, working class, and leftist struggles face many challenges.